A Portrayal of Victorian Men And Women As Seen In O'neill's “The Grand Match” - Kurnia, Nandy Intan (Journal of English and Education (JEE), 2011)
ABSTRACT  This paper analyzes the portrayal of Victorian women and men in the poem of Moira O'Neill, entitled “The Grand Match”. The poem gives the description of men and women relationship related to the discussion of love and marriage. As one of Victorian female poets, O'Neill tries to satirize the relationship of women and men by portraying the love story of a stereotypical male fortune seeker, who marries a rich woman and denies his own feeling toward a young-charming woman. This study is an attempt to show that O'Neill's female characters are not typically women commonly found in a literary text during the era in which it was written. In many ways they position themselves as a complete break from the traditional stereotyping of women, and they even can be seen as the representation of “New Woman”. In addition, through this study, the readers would be able to broaden their perspectives that although the Victorian Age was known as the era of prose, there are a lot of poems worth reading.